Optimization of the Samapta Patrol Unit to Prevent the Crime of Serious Theft in the Jurisdiction of the Jepara Police Resort (Advances in Police Science Research Journal, 2024)
The increasing number of serious theft incidents in Jepara Regency has raised concerns for the local community. To prevent such occurrences, the Indonesian National Police through the Samapta Patrol Unit of the Jepara Police Resort conducts patrol activities. This research aims to identify how the optimization of the Samapta patrol can minimize the incidence of robbery with violence in the jurisdiction of the Jepara Police Resort. Qualitative approach and field research method is applied in this study, with data collection techniques through interviews, observation, and document study. The data was analyzed through data collection, data reduction, data presentation, and conclusion drawing. The conceptual literature related to optimization, robbery with violence, crime prevention, patrol, and management theory was also used in this research. Based on the research shows that robbery with violence incidents often occur at night, with methods of breaking doors, windows, and ternit. The Samapta patrol is conducted using dialogical methods to prevent such criminal acts. The optimization of the patrol is carried out through several strategies, such as conducting joint patrols with the subordinate police station, increasing personnel from other units, and providing routine training to members to enhance their patrol activities. Additionally, a reward and punishment program is also implemented. However, the implementation of the patrol is still influenced by internal and external factors, such as the inadequate quantity and quality of personnel, lack of support for fuel and vehicle repairs, beat routes that remain the same, and patrol targets that are not in line with the development of serious theft. External factors include coordination and cooperation with related functions and the community to support the implementation of the patrol. From the results of this research, it can be concluded that the implementation of the patrol by the Samapta Patrol Unit of the Jepara Police Resort is still not optimal in preventing the crime of serious theft. The optimization of the Samapta patrol to prevent the crime of serious theft has not yet achieved optimal results. In order to minimize the incidence of such criminal acts, improvements are needed in the internal and external factors that affect the implementation of the patrol.
Keywords: TES